2011
DOI: 10.1007/s00038-011-0289-x
|View full text |Cite
|
Sign up to set email alerts
|

A model program for hepatitis B vaccination and education of schoolchildren in rural China

Abstract: This program offers an effective and sustainable model for HBV catch-up vaccination and education that can be replicated throughout China, as well as in other underserved HBV-endemic regions, as a strategy to reduce chronic HBV infection, liver failure, and liver cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…23 In agreement with such recommendations, Chinese health authorities conducted a national catch-up HBV vaccination program from 2009 to 2011. 39,40 . This program succeeded in increasing the coverage rates, which can also be observed in our results.…”
Section: Discussionmentioning
confidence: 99%
“…23 In agreement with such recommendations, Chinese health authorities conducted a national catch-up HBV vaccination program from 2009 to 2011. 39,40 . This program succeeded in increasing the coverage rates, which can also be observed in our results.…”
Section: Discussionmentioning
confidence: 99%
“…A study of HBV and liver cancer among the Asian population in the US concluded that increased health education and improved community-based interventions are necessary to prevent HBV-related liver disease in high-risk groups [ 23 ]. In China, where HBV is the primary cause of liver cancer, a total of 1925 students from 26 elementary schools were enrolled in an HBV education program; they achieved significant improvement of knowledge about the modes of transmission and protection against HBV [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several important limitations. First, we did not control for some important potential confounders such as access to health care, knowledge, attitude and practices of the providers and parents, and the socio‐economic status of the child's family . Second, the sample size used to evaluate impact of the policy was relatively small for each birth year, although the total sample size seems sufficient, which could lead to incorrect associations being reported.…”
Section: Discussionmentioning
confidence: 99%